(untitled) (Foro de Educacion, 2025)
Interculturality and higher education oriented to indigenous peoples have gained relevance in recent decades within the framework of tensions between those who demand relevant education and the State that proposes a general and homogenizing education system. In this sense, the purpose of this article is to take a brief overview of the disputes and tensions between the different actors that have been generated around the discourse of interculturality, as well as to analyze interculturality and higher education from the perspective of regulations. , especially the Academic Regime Regulations that govern Higher Education Institutions (IES) in Ecuador. For this, a documentary analysis of the regulations, national development plans, and international agreements is carried out. The preliminary results reflect that the incorporation of interculturalization policies in higher education is incipient with tensions between the actors and, on the other hand, it is strongly tied to teacher training and not to all social relationships